Implementasi Model Paikem Dan Model Pembelajaran Berbasis Masalah Sebagai Upaya Meningkatkan Prestasi Belajar Fiqih - Sri Winarsih (Universitas Alma Ata, 2015)
Abstract Learning is a process of two-way communication, the teaching is done by the teacher, while the study carried out by Student. In learning, teachers must understand the essence of the subject matter taught as a lesson that can develop students ‘ability to think and understand the various models of learning that can stimulate students’ ability to learn with careful planning by Teacher. Learning teaching is an activity designed by the teacher to help someone learn a capability or the new value in a systematic process mealui stages of design, implementation, and evaluation in the context of learning activities. Likes PAIKEM models, whereas the problem-based learning (problem-Based Learning) is: An approach to teaching that uses real-world problems as a context for students to learn about critical thinking and problem solving skills, as well as to acquire knowledge and essential concept of matter pelajaran.Prestasi learn is: Learning outcomes are expressed in terms of value or in the form of a score, after students follow learning. While objectives of this study were: (a) To determine the improvement of learning achievement once implemented Fiqh PAIKEM models and problem-based learning model. (b.) To determine the effect of learning motivation Fiqh after learning model implemented PAIKEM and problem-based learning model. (c) To enhance the provision of Fiqh learning and to increase the output satisfactory “Customer education”. This research is a class action (Classroom action research). This research class action focuses on an attempt to change the current real conditions toward the expected conditions (improvemen oriented). Research was conducted three rounds. Each round consists of four stages: design, activities and observation, reflection and revision. The targets of this research were students of class XII IPA 3 MAN Majenang Cilacap. Obtained in the form of a formative test results, observation sheet learning activities. From results of the analysis showed that student achievement increased from the first cycle of the value of the initial test to final test increased average values: 4.87 and in the second cycle of value initial tests the final test to increase the average value of values: 1.66 and an average increase in value of cycle 1 to cycle 2, namely: 5 The conclusion from this study is PAIKEM model implementation and problem-based learning model can improve learning achievement jurisprudence in class XII IPA 3 MAN Majenang Cilacap 2015-2016 school year. Keywords: Implementation, PAIKEM, problem-based learning, learning achievement.